Iran After the Bomb How Would a Nuclear-Armed Tehran Behave? - Nader, Alireza (RAND Corporation, 2013)
This study explores how a nuclear-armed Iran would behave and what this would entail for the United States and its main regional allies. It analyzes the Islamic Republic's ideology, motivations, and national security doctrine; examines a nuclear-armed Iran's potential policies toward Saudi Arabia and the GCC; discusses its potential behavior toward Israel; explores its relations with terrorist groups; and presents key findings.